Formulasi Pasta Gigi Kombinasi Ekstrak Daun Jambu Biji(Psidium guajava L) dan Daun Mint(Mentha piperita L) Serta Aktivitas Terhadap Bakteri Streptococcus mutans - Fajar Riza Harianto; Surya Sumantri Abdullah; Christel Sambou (Jurnal Lentera Farma, 2026)
Dental caries is one of the most common oral health problems, mainly caused by the bacterium Streptococcus mutans . One of the preventive efforts is the use of toothpaste containing natural antibacterial agents. Guava leaves (Psidium guajava L.) and mint leaves (Mentha piperita L.) are known to possess antibacterial activity against Streptococcus mutans . This study aimed to formulate a combination of extracts from both plants into a toothpaste preparation and to evaluate its antibacterial activity. The extracts were obtained by maceration using 96% ethanol and formulated into three formulas with a total concentration of 10%. The evaluation included organoleptic test, homogeneity, spreadability, adhesion, pH, foaming ability, and antibacterial activity test using the well diffusion method. The results showed that formula F2 (5%:5%) provided the best physical characteristics and the highest antibacterial activity, with an inhibition zone of 11.4 ± 0.9 mm, which was categorized as strong. The combination of these extracts can be formulated as an antibacterial herbal toothpaste.